Anthropometric indices significance for body fat assessment in adolescents - I. V. Ivanova; N. L. Chyornaya (Бюллетень сибирской медицины, 2010)
In order to distinguish anthropometric indices significance for body fat assessment anthropometry and bioimpedanceometry were made in 620 schoolchildren. Maximal correlation with body fat was revealed for BMI (r = 0,86). Significance of BMA in overfat diagnosis was 81,5%, specifity was 94,8%. BMA should be recommended for indirect body fat assessment during prophylactic observations in adolescents.